Tuberculous ulcer of tongue with oral complications of oral antituberculosis therapy - Ajay G; Laxmikanth C; Prashanth S (Wolters Kluwer Medknow Publications, 2006)
Tuberculosis (TB) is an infectious disease affecting humans of all ages in all parts of the world. The dentist plays an important role in the identification and control of this condition by early recognition of oral lesions that may precede the detection of the pulmonary form. Occurrence of increased incidence of mycobacterial infections as a part of the spectrum of AIDS only emphasizes the importance of early diagnosis. A case of a tuberculous ulcer on the tongue along with oral ulcerations, which occurred as a consequence of oral antituberculosis therapy (ATT), is presented. Such complications have rarely been reported in the literature and the management of these is described herein. The tuberculous ulcer healed uneventfully in five weeks after institution of ATT and the other ATT-induced ulcers healed after a week of topical anesthetic application. The clinical presentations, differential diagnoses to be considered, and management of such oral manifestations is discussed. The occupational risk posed by TB to the dentist and appropriate precautions to be observed have been highlighted.